Teaching writing for academic purposes to multilingual students instructional approaches - Bitchener, John; Storch, Neomy; Wette, Rosemary (ESL & Applied Linguistics Professional Series., 2017)
Examining what is involved in learning to write for academic purposes from a variety of perspectives, this book focuses in particular on issues related to academic writing instruction in diverse contexts, both geographical and disciplinary. Informed by current theory and research, leading experts in the field explain and illustrate instructional programs, tasks, and activities that help L2/multilingual writers develop knowledge of different genres, disciplinary expectations, and expertise in applying what they have learned in both educational and professional contexts.